2015
DOI: 10.1517/17425255.2015.1041918
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, pharmacodynamics and clinical efficacy of abiraterone acetate for treating metastatic castration-resistant prostate cancer

Abstract: It is now accepted that CRPC is not independent of androgen signaling, and targeted therapies to suppress ASA have recently been developed. With multiple high-level evidences of efficacy and safety, AA is considered a breakthrough in the treatment of mCRPC. Current clinical challenge, however, is to better delineate the mechanisms of the disease progression for developments of resistance to targeted therapies. Identification of the drug-resistance patterns would allow better patient selection for each treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
1
10
1
1
Order By: Relevance
“…1 ). Importantly, the used precursor P1, is known as abiraterone acetate (brand name Zytiga), which inhibits androgen biosynthesis and is used for treating prostate cancer 25 , with documented pharmacokinetics 26 . The fluorophores attached on a precursor P1 via 3-hydroxy group produced fluorescent probes FP-1 ‒ FP-4 or on pyridyl group via quaternization generated probes FP-5 ‒ FP-8 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 ). Importantly, the used precursor P1, is known as abiraterone acetate (brand name Zytiga), which inhibits androgen biosynthesis and is used for treating prostate cancer 25 , with documented pharmacokinetics 26 . The fluorophores attached on a precursor P1 via 3-hydroxy group produced fluorescent probes FP-1 ‒ FP-4 or on pyridyl group via quaternization generated probes FP-5 ‒ FP-8 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a minimal inhibitory effect on Pglycoprotein (P-gp) has been shown. 5,6 • A recent analysis at our institution revealed that 39% of men undergoing abiraterone+prednisone therapy used anticoagulants and/or antiaggregatory medications. 7 Cancer associated thrombosis is a leading cause of death in ambulatory cancer patients receiving chemotherapy, second only to progression of disease.…”
Section: Resultsmentioning
confidence: 99%
“…1). Importantly, the used precursor P1, is known as abiraterone acetate (brand name Zytiga), which inhibits androgen biosynthesis and is used for treating prostate cancer (25), with documented pharmacokinetics (26). The fluorophores attached on a precursor P1 via 3-hydroxy group produced fluorescent probes FP-1-FP-4 or on pyridyl group via quaternization generated probes FP-5-8 ( Fig.…”
Section: Resultsmentioning
confidence: 99%